2017
DOI: 10.1186/s40885-017-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of skin autofluorescence on high-sensitivity troponin T in hypertensive patients

Abstract: BackgroundRecent studies have reported the importance of high-sensitivity troponin T (hs-cTnT) or skin autofluorescence (AF) as a cardiovascular risk factor. However, little is known about the relationship between these two markers. The aim of this study was to clarify the clinical impact of skin AF on hs-cTnT in hypertensive patients, from the perspective of primary prevention of cardiovascular events.MethodsIn total, 457 outpatients on treatment for hypertension [182 men and 275 women; mean (± SD) age, 67 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Moreover, they also clarified that the AGEs found at the volar side of the lower arm appear to reflect the level of AGEs/RAGEs in the cardiomyocytes. In fact, there are several clinical studies that show significant relationships between skin AF and biomarkers of myocardial injury [13,34]. Although markers of myocardial injury were not evaluated in the present study, previous studies have shown that AGEs/RAGEs are believed to play important roles in the progression of myocardial injury; consequently, HFpEF patients with high skin AF may be particularly prone to becoming hospitalized due to HF.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, they also clarified that the AGEs found at the volar side of the lower arm appear to reflect the level of AGEs/RAGEs in the cardiomyocytes. In fact, there are several clinical studies that show significant relationships between skin AF and biomarkers of myocardial injury [13,34]. Although markers of myocardial injury were not evaluated in the present study, previous studies have shown that AGEs/RAGEs are believed to play important roles in the progression of myocardial injury; consequently, HFpEF patients with high skin AF may be particularly prone to becoming hospitalized due to HF.…”
Section: Discussionmentioning
confidence: 82%
“…Recent basic and clinical studies have indicated a crucial role of AGEs or receptor of AGEs for arterial aging [29-31]. Researchers have also reported the clinical usefulness of skin AF as a cardiovascular risk factor [32-34]. The present results also indicate an independent association of skin AF and PI of the CCA or the CAVI, suggesting that the accumulation of AGEs in the arterial vessel wall contributes to systemic arterial dysfunction, including that of the cerebral vessels in patients with cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that skin AF is associated with AGE-modified tissue collagen levels 38 and cardiac tissue glycation in a human study. 39 Recently, Hitsumoto 28 has shown that skin AF is an important determining factor for the elevation of the cardiac biomarker, hs-cTnT, in hypertensive patients with no history of cardiovascular events. This study found for the first time that skin AF was significantly associated with hs-cTnT but was not associated with NT-proBNP in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 A recent study revealed that skin AF is an important determining factor for hs-cTnT elevation in Japanese hypertensive patients with no history of cardiovascular events. 28 However, there have been no studies regarding the relationship between skin AF and hs-cTnT in patients with diabetes. The aim of this study is to evaluate the association between skin AF and cardiovascular biomarkers including hs-cTnT in Japanese subjects with diabetes.…”
Section: Introductionmentioning
confidence: 99%